The Role of Media Journalism in Influencing Public Perceptions of Religious Issues in the Digital Age - Saragih, M Yoserizal; Syafrizaldi; Manurung, Afwan Syahril (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2025)
This study aimed to investigate the role of journalistic media in shaping public perception of religious issues in the digital era. Using a qualitative method involving content analysis of news articles and interviews with media practitioners, the results showed that digital media platforms significantly influenced how religious discourse was constructed and consumed. Furthermore, editorial framing, selection of sources, and headline choices played a central role in shaping public opinion. Algorithmic influence and media convergence were also found to amplify the spread of both balanced and biased religious content. This study contributed to understanding media responsibility in presenting religious narratives ethically and inclusively.